FACTORS OF FORMATION AND VECTORS OF DEVELOPMENT OF THE ORGANIZATION OF REMOTE WORK IN THE WORLD - Fedotova, Tetyana (Public Management and Policy, 2025)
The article examines the urgent issue of the rapid forced growth of the volume of remote work in the world under the influence of the spread of coronavirus and against the background of the military aggression of the Russian regime with the subsequent huge migration flows that affected many countries of the world. The main problems are recognized as the unpreparedness of business entities to quickly organize workplaces at home and the lack of such experience, the impossibility of prompt redeployment of employees both in the spatial and psychological sense, as well as the lack of regulatory and legal support at the state level and local documentation on the organization of social and labor relations. The goal is to identify the main problems and factors that affect the effectiveness of the organization of remote work in modern conditions, and the prospects for the development of this trend in the world. The study used such methods as comparative analysis (both by countries and regions, and in the dynamics of years), statistical review, survey method, predictive, analytical and evaluative approach to the effectiveness of organizing social and labor relations in a remote form. Comparative analysis of the experience of different countries and companies that have achieved success in this process allowed to identify effective approaches to organizing remote work. Their practice and experience can be partially integrated in Ukraine, in which this form of labor organization has gained additional distribution due to military actions. The results of the study showed that over time, many countries and companies managed to establish effective remote work, gain some positive experience. The impact of the war is important, since the war became a prerequisite for the growth of remote work, significant changes in the structure of the labor market and personnel shortage. The article develops a predictive conceptual direction for the further development of this trend in the world and in Ukraine. The conclusions establish that improving the mechanisms for organizing remote work and its regulatory regulation is an important vector for the development of social and labor relations around the world. Future research should be aimed at studying the impact of digitalization, artificial intelligence and access to technology, as well as integrating international experience in increasing the efficiency of organizing this process in Ukraine.